2022
DOI: 10.1111/1755-6724.14981
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional Geometry and Kinematics of the Changning Anticline in the Southern Sichuan Basin

Abstract: In this study, we aim to clarify the structural characteristics and deformation process of the Changning anticline. We carefully interpret 38 two-dimensional (2D) seismic profiles in the study area and establish three-dimensional (3D) geometric and quantitative kinematic models of the Changning anticline. This study shows that the basement fault controls the formation of the Changning anticline. The fault slope of the main fault in the basement shows 'steep in the upper and gentle in the lower' structural char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…(c) Bouguer gravity anomaly (Hou & Yang, 2011); (d) Aeromagnetic anomaly (Yuan, 1996). (e) Resistivity profile obtained from magnetotelluric data (Yang, Xu, et al, 2015; Yang, Zhang, et al, 2015; Zhang et al, 2020), resistivity scale is shown at right panel, blue denotes high conductivity, and red denotes high resistivity. (f) Migration image of SRF along profile AB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(c) Bouguer gravity anomaly (Hou & Yang, 2011); (d) Aeromagnetic anomaly (Yuan, 1996). (e) Resistivity profile obtained from magnetotelluric data (Yang, Xu, et al, 2015; Yang, Zhang, et al, 2015; Zhang et al, 2020), resistivity scale is shown at right panel, blue denotes high conductivity, and red denotes high resistivity. (f) Migration image of SRF along profile AB.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, the deep structure and Mesozoic‐Cenozoic tectonic evolution are discussed by combining the RF with the density, electrical and magnetic results of the Tarim Basin. Figure 6c–e are bouguer gravity anomalies along the profile AB (Hou & Yang, 2011), reduction to pole of the aeromagnetic anomalies (Li, Li, Zhou, et al, 2014; Yuan, 1996) and a resistivity profile obtained using magnetotellurics (Yang, Xu, et al, 2015; Yang, Zhang, et al, 2015; Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation